A closed cart subscription on a Joint stock company shares (A comparative study in Iraqi and Arab legislation) (Journal of Imam Al-Kadhim College, 2023)
AbstractClosed subscription is one of the ways that many financial companies resort to for the purpose of simplifying the formal procedures imposed by law to form its capital during its establishment. This kind of subscription depends on a certain number of shareholders and those who agree with them from relatives and friends, the companies’ capital is achieved without the need for the public invitation of subscription. we did not find an explicit reference in the law of  Iraqi companies in force to this type of subscription, while previous laws and some legislations explicitly adopted this subscription in their laws. This paper  deals with the procedures of establishing joint stock company and capital and how subscription is done ,the situation of the Iraqi legislator from  closed subscription and the comparative legislations.
Keywords: Closed subscription, joint stock companies, capital